MR Angiography with Three-Dimensional Time-of-Flight and Targeted Maximum-Intensity-Projection Reconstructions in the Follow-up of Intracranial Aneurysms Embolized with Guglielmi Detachable Coils - Kähärä, Veikko J. (AJNR Am J Neuroradiol, 1999)
BACKGROUND AND PURPOSE: Intra-arterial contrast angiographies are generally used to confirm treatment results of endovascular neurointerventions such as aneurysm obliteration. We compared MR angiography with digital subtraction angiography (DSA) as a follow-up technique for the detection of aneurysmal remnant cavities and arterial patency in patients treated for intracranial aneurysms with Guglielmi detachable coils (GDCs). METHODS: In 20 consecutive patients, follow-up MR angiography and routine intra-arterial cerebral angiography were performed on the same day 1 to 7 months (mean, 4.5 months) after embolization with GDCs. MR angiographic data were postprocessed for subvolume maximum intensity projections centered on the region of the treated aneurysm. Hard copies of both imaging studies were interpreted independently in a blinded fashion to record and compare remnant cavities, location of residual flow, and adjacent arterial narrowing, using DSA as the standard of reference. The interpreters also established an occlusion grade for the treated aneurysms as evidenced on DSA images and evaluated MR angiograms for artifactual effects. RESULTS: Overall sensitivity and positive predictive value of MR angiography in revealing aneurysmal remnant cavities were both 90%. Specificity in ruling out a remnant cavity with MR angiography was 91%. One remnant cavity was missed by MR angiography, and in five patients, false adjacent arterial encroachments were reported. CONCLUSION: MR angiography may be useful in the long-term follow-up of successfully treated small and medium-sized aneurysms after concurrent primary verification of their occlusion with DSA.